Solvent effects on tautomerics equilibria in β-ketonitriles: NMR and theoretical studies - Ruiz, Danila Luján (2010)
Solvent effects on tautomeric equilibria in several b-ketonitriles has been investigated using nuclear magnetic resonance (NMR) spectroscopy and theoretical methods. The experimental chemical shifts were compared with theoretical values obtained by using gauge-including atomic orbital (GIAO) calculations, implemented at Density Functional Theory (DFT) level with hybrid functionals, B3LYP calculations. The solvent effect on the calculated structures has been taken into account through the polarized continuum model (PCM) for chloroform, acetone and dimethyl sulfoxide (DMSO). Also, some structural parameters were calculated in gas phase and in three different solvents.